Best Answer

3/2x = 9

Multiply both sides by 2x: 3 = 18x

Divide both sides by 18: 1/6 = x, that is x = 1/6 = 0.166...

Q: 3 2x 9 how to solve?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x - 3= 9 x=

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

Where is y in this equation? 2x-3=9. First, you add 2 to both sides, and you get 2x=12. Divide both sides by 2; so, x=6.

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

Related questions

2x-3=9 so 2x=12 and x=6

2x - 3= 9 x=

4x2 - 9 = (2x + 3)(2x - 3)

2x + 3= 9.X=

2x+3=9 x

3

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

Please help me solve this 2x + 3 = 9 x =. x=3 because 2x3=6+3=9

-9-2x=9-8x6x=18 x=3

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3

2x + 3 = 9. What you need to do first, is to isolate the 'x' by itself. Subtract the 3 to the other side. 2x + 3 = 9. (Before subtraction) 2x = 6 (After subtraction) Then you can divide by whatever is on the 'x'. In this case, it is 2. (Before) 2x = 6 (After) x = 3. Now you can check the problem, so put in 3 for x. 2x + 3 = 9. 2(3) + 3 = 9. 6 + 3 = 9. 9 = 9.